IMPLEMENTATION OF PARKING SERVICE RETRIBUTION POLICY ON THE EDGE OF PUBLIC ROADS OF SUKABUMI CITY - Putri, Delia Arsa Aulia; Amirulloh, M Rijal; Mulyadi, Andi (DIA: Jurnal Administrasi Publik, 2023)
The title of this study is "Implementation of the Policy for Parking Service Charges on the Side of Public Roads in the City of Sukabumi". The purpose of this study is regarding parking services on public roads. This research found several problems, namely the ticket was not realized when collecting parking fees and the lack of Human Resources (HR) in supervising parking attendants. The method used in this research is using qualitative research with data collection techniques using observation, interview and documentation techniques. In determining the informants in this study using the Snowball Sampling technique. The theory applied in this research is the policy implementation theory of Donald S.Van Meter and Carl E.Van Horn which is influenced by 6 dimensions. The results of implementing this policy conclude that the Implementation of Policy on Regional Regulation Number 16 of 2011 Regarding Parking Service Fees on the Side of Public Roads in the City of Sukabumi, that there are policies that have not obtained optimal results in line with the goals and objectives that have been set. If you look at the number of tickets that were not given and the lack of supervision.